Behavior of alkali-activated slag in the presence of different aluminosilicate sources. Issue 3 (4th May 2017) - Amer, A. A.
Abstract: This article presents an investigation into the performance of alkali-activated slag (AAS) in the presence of different aluminosilicate sources. AAS was individually replaced by 10, 20, and 30 wt. % Metakaolin (MK), Ground ceramic waste (GCW) and ground clay brick waste (GCBW). The results showed that the Na2 O/Al2 O3 and CaO/SiO2 molar ratio play a crucial role in the behavior of AAS. GCW and GCBW with different contents have positive impact on the compressive strength of AAS, especially at later ages of curing. AAS performed well in the presence of 10 wt. % MK. Meanwhile, 20 and 30 wt. % caused the AAS compressive strength regression. The water demand of AAS increased with an increase in aluminosilicate's weight percentage. Also, AAS containing GCBW showed the shortest setting times as well as the highest mechanical properties as proved by XRD, FTIR, and SEM.